2008
DOI: 10.1038/mp.2008.120
|View full text |Cite|
|
Sign up to set email alerts
|

Differential effects on T-cell function following exposure to serum from schizophrenia smokers

Abstract: Cigarette smoking is more prevalent in subjects with schizophrenia compared to those with other psychiatric disorders or the general population and could therefore affect molecular pathways that impact the pathophysiology of this disorder. As smoking is also known to suppress immune responses, we investigated the effects of 'smoking-conditioned' serum obtained from schizophrenia and control subjects on healthy T cell in vitro. We found that T-cell proliferation was significantly increased following exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Cigarette smoking has been recently shown to have selective effects on serum components of patients with schizophrenia that lead to altered immune function different from healthy controls (Herberth et al, 2010). This might partly explain the specific effect of nicotine use on IL-6, and the lack of its effect on cytokine levels in our group of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking has been recently shown to have selective effects on serum components of patients with schizophrenia that lead to altered immune function different from healthy controls (Herberth et al, 2010). This might partly explain the specific effect of nicotine use on IL-6, and the lack of its effect on cytokine levels in our group of healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Unstimulated PBMCs from antipsychotictreated (AT) chronically ill schizophrenia patients were also investigated by LC-MS E to determine which markers may be normalized by treatment and which may be indicators of the underlying disease state. PBMCs were chosen as the tissue source in this study due to reports of immune dysfunction in schizophrenia patients 9,10 and as previous studies have shown that such cells are useful peripheral sources of biomarkers for studies of psychiatric illnesses. 11,12 In addition, numerous studies have shown that the brain and blood cells show a number of parallel responses, which suggest that the PBMCs may be a useful surrogate of brain function.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of antipsychotic administration on white matter integrity appear inconsistent and are more poorly defined, but there is some evidence for enhanced myelination via effects on oligodendrocytes 67 , 68 . Finally, rates of PP are higher in non-smokers than in smokers with bipolar disorder [69] ; this is interesting since smoking boosts numbers and/or function of Tregs in the large airways and lungs (and possibly other tissues) 70 , 71 and reduces Ccn3 expression in these tissues in a model system [72] .…”
Section: Modulation Of the Treg–ccn3–myelin Axis By Risk And Protectimentioning
confidence: 99%